The influence of political connections, corporate governance, and financial distress on tax aggressiveness - Hartiaman, Fahmi; Murtanto, Murtanto (WIM Solusi Prima, 2025)
Tax aggressiveness is a common practice among companies aiming to minimize their tax burdens through various tax planning strategies. This study investigates the influence of political connections, corporate governance, and financial distress on tax aggressiveness. The research focuses on consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) as the sample. Political connections are measured using a dummy variable, corporate governance is measured using the Global Reporting Initiative (GRI) Standards Content Index 2021, while financial distress is measured using the Altman Z-Score (non-banking). Tax aggressiveness is proxied by the effective tax rate (ETR). The findings indicate that political connections have a negative and significant effect on tax aggressiveness. This suggests that companies with political ties tend to engage less in aggressive tax planning, possibly due to higher scrutiny from regulators or reputational concerns. In contrast, corporate governance is found to have a positive and significant impact on tax aggressiveness. Meanwhile, financial distress does not show a significant effect on tax aggressiveness. This study contributes to the literature on tax aggressiveness by providing empirical evidence on the role of political connections, corporate governance, and financial distress in shaping corporate tax behaviour.